2019
DOI: 10.19044/esj.2019.v15n27p362
|View full text |Cite
|
Sign up to set email alerts
|

Géographie du Paludisme dans la région de Libreville-Owendo-Akanda, Gabon

Abstract: In order to determine the geography of malaria, to know the spatial distribution of health facilities and to identify malaria risk areas in Libreville-Owendo-Akanda area, a study was conducted from july 2016 to june 2017. This study consisted of collecting hospital morbidity data and characterizing public and private health structures in the study area. The malaria data were collected in the clinics using the pre-designed and tested collection forms. than in the neighborhoods of the two other neighboring commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…Most respondents used ITNs throughout the year and this could be due to the annual aggressivity pattern of mosquitoes that makes them use this approach all the time. This observation corroborated the finding of Maghendji-Nzondo et al (2016) and Mbouloungou et al (2019) that malaria cases occurred throughout the year with peak in the short rainy season. We found that most respondents purchased ITNs themselves and only few individuals were provided to them free.…”
Section: Discussionsupporting
confidence: 92%
“…Most respondents used ITNs throughout the year and this could be due to the annual aggressivity pattern of mosquitoes that makes them use this approach all the time. This observation corroborated the finding of Maghendji-Nzondo et al (2016) and Mbouloungou et al (2019) that malaria cases occurred throughout the year with peak in the short rainy season. We found that most respondents purchased ITNs themselves and only few individuals were provided to them free.…”
Section: Discussionsupporting
confidence: 92%
“…Akanda covers an area of 45,482 hectares and is part of the departement du Komo-Mondah, in the province de l'Estuaire. It includes two boroughs divided into 15 districts [14]. There are several socio-economic activities including trading, sports, health, education, and tourism.…”
Section: A Study Areamentioning
confidence: 99%
“…In Gabon, malaria is hyper-endemic (Maghendji-Nzondo et al, 2016a;Pamba et al, 2020) and its transmission occurs throughout the year (Bouyou-Akotet et al, 2012). It is the leading cause of hospital consultations where 45% of hospitalized people are children and 71% are pregnant women (Mbouloungou et al, 2019). In Gabon, the towns with high infection prevalence with malaria include: Lastourville (79.5%), Fougamou (53.6%), Oyem (44.2%), Koulamoutou (36.1%), Libreville (24.1%) and Franceville (22.00%) (Mawili-Mboumba et al, 2013;Maghendji-Nzondo et al, 2016a, b;Minsanté-SNIS, 2016;Minsanté-SNIS, 2018).…”
Section: Introductionmentioning
confidence: 99%